Melacak Akar Masalah Pornografi dan Pornoaksi serta Implikasinya terhadap Nilai-nilai Sosial (Kajian Filsafat Nilai) - Supartiningsih Supartiningsih (Jurnal Filsafat "WISDOM", 2004)
Pornography and pornoaction represent two social probelms, and yet they remain an open question. The effort to solve these probelms is even partial and unserious. This paper is intended to deal with these probelm and in doing so, it will trace their roots and analyses their implications to social values.Pornography and pornoaction are a form of sexual exploitanion as they reduce the full dimension of sexuality. They both ignore such other sexual dimensions as behavioral, psychosocial, and clinical, while limit themselves on the sexual organs.They are rooted in patriarchal culture, and commercialism. Representing patriarchal propaganda, they place women as mere property or servant of man. Moreover, patriarchal propaganda meets commercialism as sexuality is also connected to the economic system of production, distribution, and transcation of sexual fantasy. In turn, this economic system transforms itself into libidonomics, that is the distribution system of stimulus, persuasion, pleasure, and passion in society. The implication is that they challenge social structure with its moral values.